Juridical Analysis of Criminal Liability for Perpetrators of Public Indecency: A Study of Simalungun District Court Decision No. 314/Pid.Sus/2022/PN.SIM - Alfred Ndraha; Desy Kartika C. Sitepu; Novelina Mutiara S Hutapea; Satria Chandra (Journal Analytica Islamica, 2023)
The crime of violating decency in front of another person in Article 281 first and second of the Criminal Code is the prohibition of violating decency in public - namely in a public place or in a place that is not a public place but can be seen/heard from a public place -, or in front of another person against his/her will. The definition of violating decency is a violation of manners in the sexual field, where the act of violating decency can generally cause feelings of shame, feelings of disgust or stimulation of people's lust. Immoral acts are one of the problems that are quite concerning. Judging from the various cases, be it cases of sexual abuse, adultery or same-sex relationships, it has become a serious problem. The perpetrators of immoral crimes today are no longer just adults, but even minors have many cases as perpetrators of immoral crimes. This is influenced by various things, one of which is due to the easy access to pornographic videos on social media.